The Impact of Employee Communication and Perceived External Prestige On Organizational Identification - Smidts, Ale; Pruyn, Ad Th. H.; Riel, Cees B. M. Van (Academy of Management Journal, 2001)
Employees' Organizational Identification (OI) is measured in a customer service organization. Particularly the effects of employee communication and perceived external prestige (PEP) on OI were evaluated. Results show that employee communication affects OI more strongly than PEP. One aspect of employee communication, the communication climate, appears to play a central role: it mediates the impact on OI of the content of employee communication. These results suggest that the importance of how an organization communicates internally is even more vital than the question what is being communicated. Consequences of the results for managing and synchronizing internal and external communication are discussed. Employees who identify strongly with their organization are more likely to show a supportive attitude toward it (Ashforth & Mael, 1989), and to make decisions that are consistent with organizational objectives (Simon, 1997: 284). Organizational identification may induce employees to...